Avoidable Acute Care Use Associated with Nausea and Vomiting Among Patients Receiving Highly Emetogenic Chemotherapy or Oxaliplatin. (21st December 2020) - Navari, Rudolph M.; Ruddy, Kathryn J.; LeBlanc, Thomas W.; Nipp, Ryan; Clark‐Snow, Rebecca; Schwartzberg, Lee; Binder, Gary; Bailey, William L.; Potluri, Ravi; Schmerold, Luke M.; Papademetriou, Eros; Roeland, Eric J.
Abstract: Purpose: Chemotherapy‐induced nausea and vomiting (CINV) contributes to avoidable acute care, a metric now tracked in Medicare's oncology outcome measure. CINV is preventable, yet guidelines are often not followed. We sought to quantify acute care involving CINV and other avoidable toxicities after highly emetogenic chemotherapy (HEC) to identify excess risk and assess clinician adherence to antiemesis guidelines for HEC. Materials and Methods: We retrospectively evaluated U.S. electronic health records (2012‐2018) using Medicare's OP‐35 outcome measure to identify avoidable acute care involving any of 10 toxicities, including CINV, after HEC regimens relative to non‐HEC. Antiemetic guideline adherence was defined as use ofneurokinin‐1 (NKl) receptor antagonists Q5 (RAs) plus 5‐hydroxytryptamine type 3 RA+ dexamethasone at HEC initiation. Results: Among 17, 609 patients receiving HEC, acute care rates associated with HEC chemotherapy included 32% cisplatin, 31% carboplatin, and 21% anthracycline/cyclosphospharnide (AC), with 76% meeting the criteria as avoidable events. Oxaliplatin rates were 29%. Avoidable acute care occurred 1.83 times (95% confidence interval, 1.76‐1.91, p < .0001) as often after HEC versus non‐HEC excluding oxaliplatin; CINV‐related acute care occurred 2.29 times as often. Nonadherence to antiemesis guidelines occurred in 34% and 24% of cisplatin and AC courses, respectively, because of omission of a NKl RA. Conclusions: Patients treated with HEC regimens experienced high avoidable acute care use, 1.8 times the risk seen for other chemotherapy. Nonadherence to guideline‐directed antiemetic prophylaxis highlights the need to ensure adherence to antiemetic guidelines, including the use of NKl RA in HEC. Implications for Practice: After survival, perhaps the most important goal in oncology is limiting avoidable acute care, a goal now used by Medicare to impact cancer reimbursement. This study found that patients treated with highly emetogenic chemotherapy (HEC) regimens had high rates of avoidable acute care use, 1.8 times the risk seen for other chemotherapy. A substantial proportion of the avoidable acute care involved chemotherapy‐induced nausea and vomiting. Results showed that incomplete adherence to national antiemetic guidelines for HEC regimens primarily driven by omission of upfront neurokinin‐1 receptor antagonist use, suggesting that improved adherence can meaningfully resolve this gap in quality and cost of care. Abstract : Reducing avoidable acute care services, such as emergency department visits, can improve cancer care and reduce cost. This article reports rates of postchemotherapy acute care use, focusing on chemotherapy‐induced nausea and vomiting in patients treated with highly emetogenic chemotherapy.